2010
DOI: 10.1093/hmg/ddq468
|View full text |Cite
|
Sign up to set email alerts
|

Defective gonadotropin-releasing hormone neuron migration in mice lacking SEMA3A signalling through NRP1 and NRP2: implications for the aetiology of hypogonadotropic hypogonadism

Abstract: Kallmann syndrome (KS) is a genetic disease characterized by hypogonadotropic hypogonadism and impaired sense of smell. The genetic causes underlying this syndrome are still largely unknown, but are thought to be due to a developmental defect in the migration of gonadotropin-releasing hormone (GnRH) neurons. Understanding the causes of the disease is hampered by lack of appropriate mouse models. GnRH neurons are hypothalamic cells that centrally control reproduction in mammals by secreting the GnRH decapeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 33 publications
8
153
1
3
Order By: Relevance
“…All but one mutation were very rare. Eight mutations were shown to be loss-of-function, which confirms the model observed in Sema-3A knockout mice [2]. However, these heterozygous mutations do not fully explain the KS phenotype.…”
supporting
confidence: 55%
“…All but one mutation were very rare. Eight mutations were shown to be loss-of-function, which confirms the model observed in Sema-3A knockout mice [2]. However, these heterozygous mutations do not fully explain the KS phenotype.…”
supporting
confidence: 55%
“…Involvement of SEMA3A in T-cell differentiation may explain the early liability to infections in the patient [Garcia et al, 2011]. Finally, a heterozygous intragenic SEMA3A deletion was recently observed in a father and his two children with signs of Kallmann syndrome (hypogonadotropic hypogonadism and anosmia) and supported by the mouse findings of Cariboni et al [2011] was considered causative . However, a study of SEMA3A mutations in 386 patients with Kallmann syndrome suggested that monoallelic mutations in SEMA3A were not sufficient to induce the abnormal phenotype, but may contribute to the pathogenesis of Kallmann syndrome through synergistic effects with mutant alleles of other disease-associated genes [Hanchate et al, 2012].…”
Section: Discussionmentioning
confidence: 81%
“…However, while the patient only had a minor structural heart anomaly and normal intellectual development, knock-out mice commonly die from heart failure and show abnormal neuronal architecture which was considered a correlate of lissencephaly [Behar et al, 1996] and Kallmann syndrome [Cariboni et al, 2011]. Therefore, the preserved $20% expression of an apparently grossly functioning protein in the patient may be sufficient to maintain cortex and heart function.…”
Section: Discussionmentioning
confidence: 99%
“…Гипоталамические ГнРГ-нейроны в отличие от других нейронов, высвобождающих гормоны, фор-мируются вне мозга [6]. Число нейронов, продуци-рующих ГнРГ в гипоталамусе человека, относитель-но мало (<2000).…”
Section: Abstract: Isolated Hypogonadotropic Hypogonadism Kallmannunclassified
“…Недостаток белка ухудшает расположение нейронов ГнРГ в гипоталамусе, что приводит к нарушению нейроэндокринного меха-низма регуляции полового развития [6].…”
Section: проблемы эндокринологии 6 2014unclassified